Paleoceanographic reconstructions from planktonic foraminifera across the Cenomanian/Turonian boundary and OAE 2 at southern high latitudes (IODP Site U1516, Mentelle Basin, Indian Ocean, SW Australia) - Maria Rose Petrizzo; David K. Watkins; Kenneth G. MacLeod; Takashi Hasegawa; Brian T. Huber; Sietske J. Batenburg; Tomonori Kato (Copernicus, 2021)
Planktonic foraminifera distributions registering the environmental changes across the Cenomanian-Turonian boundary interval is presented from the Integrated Ocean Discovery Program (IODP) Expedition 369 Site U1516 in the Mentelle Basin (Indian Ocean, SW Australia). Site U1516 was located at 60°-62°S paleolatitude and it is the first high latitude locality in the Southern Hemisphere where planktonic foraminifera are consistently recorded across the Oceanic Anoxic Event 2 (OAE 2) interval and its associated positive 13C excursion. Planktonic foraminifera and calcareous nannofossil biostratigraphy and stable isotopic results indicate the presence of a hiatus in the upper Cenomanian that spans the base of the 13C excursion, thus the record of the onset of OAE 2 is not preserved. Nevertheless, correlation between the 13C and 18O profiles at Site U1516 and the European reference section at Eastbourne (England) allow identification of the Carbon Isotopic Excursion and, tentatively, of correlative local cooling consistent with the expression of the Plenus Cold Event at low latitudes. Absolute abundances of planktonic and benthic foraminifera, and radiolaria combined with δ13C and δ18O measurements of both bulk carbonate and different species of planktonic and benthic foraminifera provide clues concerning the paleoceanographic changes across OAE 2. In the lower part of OAE 2 and coinciding with the trough in the 13C profile, the planktonic foraminiferal assemblages are dominated by small-sized (125-38 m) opportunistic species and radiolaria indicating a dominantly eutrophic regime. The presence of abundant benthic foraminifera may indicate a local increase of oxygenation during the interval of the Plenus Cold Event associated to high δ18O values as observed at low latitudes. At Site U1516, the middle part of OAE 2 that corresponds to the plateau phase of the 13C profile is masked by absence of carbonate, highest TOC values and high biogenic silica indicating this interval corresponded to a time of highly stressed ...